Drying Profile and the Mineral Content in Quality Determination of Kappaphycus Alverezii (Rhodophyceae) from Semporna, Sabah, Malaysia - Kamarul 'Ain, Mustafa; Conniey, Fay Komilus (2018)
This study was carried out to determine the mineral bioavailability of Kappaphycis alverezi in different solution and to obtain the drying condition for seaweed to achieve the acceptable level of moisture content of 40%. Acetic acid, sodium chloride and water are the parameters used in the mineral availability analysis to see the percentage of solubility after been subjected using Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES). Results showed that Kappaphycis alverezi treated with acid has a significantly increased in solubility of calcium which were 77.65, 63.64 and 60.02% respectively. In the drying experiment, the fresh seaweed and the commercial seaweed were dried in a cabinet dryer to study drying time to achieved the desired moisture content. The result based on drying showed that temperature have a significant difference (p>0.05) in drying time and the best drying temperature was 40°C in retaining the seaweed quality after the seaweed were subjected to syneresis analysis. The syneresis analysis demonstrated that 40°C had a lowest syneresis percentage which was 3.10% compared to temperature 60, 80 and 100°C at 11.51, 16.61 and 18.89% respectively. Proximate analysis showed that moisture content in Kappaphycis alverezi was 56.69% and ash content (26.34%), crude fibre (9.77%), protein (3.13%) and fat (0.67%). In dietary fibre analysis, by using enzymatic gravimetric method to determine the total dietary content in seaweed showed that seaweed can be classified as a high source of dietary fibre as the total dietary fibre obtained was 56.29 %.